2015
DOI: 10.1007/s11084-015-9468-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of a “Miller-Type” Complex Prebiotic Broth

Abstract: In a famous experiment Stanley Miller showed that a large number of organic substances can emerge from sparking a mixture of methane, ammonia and hydrogen in the presence of water (Miller, Science 117:528-529, 1953). Among these substances Miller identified different amino acids, and he concluded that prebiotic events may well have produced many of Life's molecular building blocks. There have been many variants of the original experiment since, including different gas mixtures (Miller, J Am Chem Soc 77:2351-23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…In previous work (Scherer et al 2017, Wollrab et al 2016 we showed that oxygen reservoirs appear to build up in the broth, likely in form of peroxides, a direct product from oxygen diradicals created in the discharge. These can even release oxygen radicals (Scherer et al 2017).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In previous work (Scherer et al 2017, Wollrab et al 2016 we showed that oxygen reservoirs appear to build up in the broth, likely in form of peroxides, a direct product from oxygen diradicals created in the discharge. These can even release oxygen radicals (Scherer et al 2017).…”
Section: Discussionmentioning
confidence: 82%
“…While small molecules with elevated vapor pressure essentially remain in the gas phase and remain subject to further discharge, larger and more polar molecules are more likely to dissolve in the liquid phase where they may react further. A previous analysis showed that the Miller-Urey experiment produces many molecules with unsaturated (triple or double) bonds in the gas and in the liquid parts of the broth (Scherer et al 2017, Wollrab et al 2016. These unsaturated bonds tend to react further.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple molecules (H 2 O, CO, NH 3 , CH 4 ) along with complex ones were available on Earth from the early stages of its formation, but it seems that Earth's collision with a Mars-sized body, about 4.5 billion years ago which formed the Moon, removed its pristine atmosphere. 15 This kind of atmosphere did not easily yield amino acids after being exposed to ionizing agents, like UV radiation or electrical sparkling; 16 however the synthesis could have been much improved by buffering reaction solution (CaCO 3 ) and lowering of its oxidation potential (Fe 2+ ). 17 For the prebiotic synthesis and eventually emergence of life, it was also necessary to provide suitable geological habitat (increased concentration, temperature or pressure etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[1] Since that landmark work, several further studies have explored similar systems and brought more advanced analytical techniques to bear on the complex product mixtures produced, as well as arguing if ar educing atmosphere could be realistic for the early Earth. [2][3][4] As with many such experiments,the Miller-Urey reaction has been typically performed in sealed clean glassware with asmall number of pure reagents,whereas life emerged in afar more complex and heterogeneous environment. [5] However, even this simple system produces alarge and diverse range of products,t hought to be resulting from ac ombinatorial explosion of simple uncontrolled reactions,a nd their study is limited due to their perceived analytical intractability.…”
mentioning
confidence: 99%